PENTINGNYA MENUNTUT ILMU DALAM TAFSIR AYAT AL QURAN - Henny Oktaviyenna; Trinita Hemalia Putri (Proceeding International Seminar of Islamic Studies, 2022)
Every want of us who wants about the world,whether its desire to get a job,position,property and so on must be with knowledge or intelligence,without having knowledge it is impossible for someone to get what he wants. Likewise with life after death or afterlife. If you want to get happiness in the hereafter in the form of the pleasure of Allah,meet direcly with Allah SWT,and get heaven then all of that must also be with knowledge. Or if we want both, namely to get world and the hereafter,than that too must be with knowledge.